(untitled) (Jurnal Anestesi Perioperatif, 2020)
Krisis miastenia adalah eksaserbasi akut miastenia gravis dengan kelemahan yang melibatkan otot-otot pernapasan sehingga terjadi kegagalan napas akut dan memerlukan dukungan ventilasi mekanik. Krisis miastenia merupakan komplikasi miastenia gravis yang paling berbahaya dan mengancam jiwa bila tidak segera ditangani. Timbulnya krisis miastenia dapat dipicu oleh berbagai faktor, di antaranya infeksi dan penggunaan antibiotik aminoglikosid. Tata laksana Intensive Care Unit (ICU) pasien krisis miastenia meliputi tata laksana terhadap kegawatan respirasi, tata laksana terhadap miastenia gravis, dan tata laksana terhadap faktor peyulit. Intubasi endotrakeal dan dukungan ventilasi mekanis merupakan pilihan utama tata laksana kegawatan respirasi. Plasmaparesis adalah salah satu metode terapi yang terbukti efektif dan efisien selain pemberian agen anticholinesterase, terapi imunomodulator cepat, agen imunosupresif, dan timektomi. Terapi standar untuk menanggulangi tuberkulosis paru dengan obat antituberkulosis berdasar atas pedoman penatalaksanaan tuberkulosis serta terapi ventilator associated pneumonia (VAP) dengan pilihan antibiotik sesuai dengan hasil kultur bakteri. Dukungan nutrisi yang adekuat juga diperlukan untuk menunjang keberhasilan terapi. Dengan assessment dini dan terapi yang adekuat diharapkan dapat memperbaiki prognosis pasien krisis miastenia. Pada laporan kasus ini kami sajikan tata laksana ICU pasien krisis miastenia gravis yang dipicu oleh tuberkulosis paru dengan penyulit VAP yang dirawat di ICU RSHS Bandung pada bulan Oktober–November 2019. ICU Management of Myasthenic Crisis in Pulmonary Tuberculosis Patients with Ventilator Associated Pneumonia Complications Myasthenic crisis is an acute exacerbation of myasthenia gravis with a weakness that involves the respiratory muscles, leading to acute respiratory failure that requires mechanical ventilation support. Myasthenia crisis is the most dangerous and life-threatening complication of myasthenia gravis if not treated immediately. The emergence of myasthenic crisis can be triggered by various factors, including infection and aminoglycoside use. Intensive Care Unit (ICU) management of myasthenic crisis patients includes management of respiratory emergencies, management of myasthenia gravis, and management of complicating factors. Endotracheal intubation and mechanical ventilatory support are the main choices in the management of respiratory emergencies. Plasmaparesis is one of the proven and effective therapeutic methods in addition to anticholinesterase agent, rapid immunomodulatory therapy, immunosuppressive agent, and thymectomy. Standard therapy for treating pulmonary tuberculosis includes anti-tuberculosis drugs, as stated in tuberculosis management guidelines, and Ventilator Associated Pneumonia (VAP) therapy with antibiotic options according to bacterial culture results. Adequate nutritional support is also needed to support the success of therapy. With early assessment and adequate therapy, it is expected that the prognosis of myasthenic crisis patients will be improved. This case report presented the management of myasthenia gravis crisis triggered by pulmonary tuberculosis with VAP complications in patients treated at the ICU of Dr. Hasan Sadikin General Hospital Bandung, Indonesia, from October to November 2019.